1999
DOI: 10.1046/j.1365-2249.1999.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of theLeishmania infantumhistones H2B and H4 during canine viscerocutaneous leishmaniasis

Abstract: SUMMARYIn this study we show that sera from dogs naturally infected with Leishmania infantum contain antibodies that specifically react against the parasite H2B and H4 histones. The Leishmania H2B and the amino-terminal region of the histone H4, expressed as fusion proteins, when confronted with sera from canine viscerocutaneous leishmaniasis (VCL) dogs, were recognized by 63% and 47%, respectively. No reactivity was detected when sera from dogs naturally infected with pathogens other than Leishmania were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 30 publications
3
47
0
1
Order By: Relevance
“…Interestingly, humoral immune responses against histone H2b were recently reported in dogs with canine VL. Abs to histone H2b as well as other members of the histone family were detected after the dogs developed VL due to a Leishmania infantum infection (35,36). These data suggest that histone H2b is available for immune recognition not only in situations where the immune system has controlled the infection but also in situations where the parasite has evaded protective immune mechanisms.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, humoral immune responses against histone H2b were recently reported in dogs with canine VL. Abs to histone H2b as well as other members of the histone family were detected after the dogs developed VL due to a Leishmania infantum infection (35,36). These data suggest that histone H2b is available for immune recognition not only in situations where the immune system has controlled the infection but also in situations where the parasite has evaded protective immune mechanisms.…”
Section: Discussionmentioning
confidence: 82%
“…One drawback of serological assays with whole parasites is the existence of cross-reactivity with other pathogens, including Trypanosoma cruzi, mycobacteria, malaria parasites, or amoebae, which are coendemic with Leishmania in many parts of the world (7,51). The performance of serodiagnostic assays could be improved by using purified or recombinant leishmanial antigens, such as gp63 (40,41,56), Hsp70 (30,48), p94 (53), gp70 and p72 (24), p32 (61), rK39 (2,11), r gene B protein (rGBP) (15,31), H2A and H2B (31,57,58,59), rLACK (31), and the promastigote surface antigen 2 (rPSA-2) (18,31,37), or synthetic peptides (14,48) and antigens from promastigote-conditioned media (33).…”
mentioning
confidence: 99%
“…The subsequent characterization of histone H3, strongly recognized by CVL sera, showed that this parasite owns the most divergent histone H3 described to date (34). It was also demonstrated that the other two histones, H2B and H4, belonging to the nucleosomal core of L. infantum are recognized by CVL sera (36). In addition, antibodies against rH2A and rH2B were detected in the sera of a large group of VL patients (22,24,29).…”
mentioning
confidence: 85%